Fabrication of targeted gold nanoparticle as potential contrast agent in molecular CT imaging - Malekzadeh, Reza; Ghorbani, Marjan; Faghani, Parsa; Abdollahi, Behnaz Babaye; Mortezazadeh, Tohid; Farhood, Bagher (Journal of radiation research and applied sciences, 2023)
Trastuzumab (TZ) multifunctional Fe3O4 coated gold nanoparticles (Au NPs) through polyethylene glycol (PEG) linking for targeted molecular computed tomography (CT) imaging was developed. The prepared TZ-PEG-Fe3O4@Au NPs were fully characterized and cytocompatibility, X-ray attenuation measurement, and in vitro cell targeting ability were analyzed. The findings showed that the synthesized NPs, with a size of less than 100 nm, were non-toxic at specific concentration ranges, and exhibit better X-ray attenuation intensity than iodine-based contrast agents at the same concentration. The created targeted NPs can be employed as a contrast agent for molecular targeted CT imaging of cancer cells expressing the human epidermal growth factor receptor 2 (HER-2).